2009
DOI: 10.1007/s10681-009-0100-8
|View full text |Cite
|
Sign up to set email alerts
|

Genotype by environment interactions in wheat quality breeding programs in southeast Europe

Abstract: The objective of this study was to determine genotype 9 environment interactions (GEI) obtained in wheat production in southeast Europe for protein content, sedimentation value, and loaf volume. Twenty wheat genotypes divided in two groups with different combinations of high molecular weight glutenin subunits (HMW-GS) were analyzed in 15 environments (E). In a combined analysis of variance, effects of genotype, environment, and their interaction (GEI) were highly significant for almost all the analyzed traits.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
1
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(56 citation statements)
references
References 33 publications
2
43
1
4
Order By: Relevance
“…AMMI analysis showed 6-47 % contribution from GEI to total variation in terms of 1 to 4 principal component axes (Prashant et al 2015 ). Similarly, Hristov et al ( 2010 ) showed signifi cant GEI contribution to LV, SV and GPC by AMMI analysis. It is possible that GEI could infl uence correlations among LV and its predictive tests thereby making it necessary to examine them individually in year-location combinations.…”
Section: Contributions Of G E and Gei Effects For Drt And Bmq Traitsmentioning
confidence: 82%
“…AMMI analysis showed 6-47 % contribution from GEI to total variation in terms of 1 to 4 principal component axes (Prashant et al 2015 ). Similarly, Hristov et al ( 2010 ) showed signifi cant GEI contribution to LV, SV and GPC by AMMI analysis. It is possible that GEI could infl uence correlations among LV and its predictive tests thereby making it necessary to examine them individually in year-location combinations.…”
Section: Contributions Of G E and Gei Effects For Drt And Bmq Traitsmentioning
confidence: 82%
“…Genotypes on the highest point in certain sections of the graph have the best results in environments located in the same section (Figure 2) (Yan, 2001, Gvozdanović-Varga, et al 2004, Hristov et al, 2010. A large group of genotypes (Banacanka, Samurai, Oktavija, Jana, UM-1, UM-2, UM-5, UM-6, UM-9, UM-10, and UM-11), with average seed yield per plant close to the general mean of 7.41 g, are distinguished on the biplot.…”
Section: Resultsmentioning
confidence: 99%
“…Hard leathery chaff protects the kernel from air pollution and pests, making spelt suitable for ecological (organic) farming (Glamoclija et al, 2015). Hristov et al (2010) point out that, increating new cultivars, we do not use enough of positive traits of rare cultivars and populations and their relative swith high genetic variability, which we are extra ordinary rich in. Plant breeding is about accumulating a number of desirable genes and combining them into one genotype (Pavićević, 1985(Pavićević, , 1988.…”
Section: Introductionmentioning
confidence: 99%